2021
DOI: 10.3390/su132413951
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Applicability of the Safe-by-Design Concept: A Theoretical Case Study Using Polymer Nanoclay Composites for Coffee Capsules

Abstract: The production and use of engineered nanomaterials and nano-enabled products is increasing, enabling innovations in many application areas, e.g., in the sector of food contact materials. However, nanosafety-relevant information for chemical risk assessment is still scarce, leading to a high level of uncertainty and making the early integration of safety to the innovation process indispensable. This study analyzed the strengths, weaknesses, and applicability of the nano-specific Safe-by-Design (SbD) concept usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The detailed results of our literature review can be found in the sheet 'review of conceptual S(S)bD lit' of the ESI. † It appears that 5 out of 20 reviewed studies use both the terms SbD and SSbD, 15,37,38,40,45 and another 4 studies add sustainability assessments to safety assessment without mentioning the term SSbD explicitly. 1,6,36,47 Another general finding is that most (18 out of 20) of the reviewed studies focus on engineered nanomaterials (ENMs) and nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed results of our literature review can be found in the sheet 'review of conceptual S(S)bD lit' of the ESI. † It appears that 5 out of 20 reviewed studies use both the terms SbD and SSbD, 15,37,38,40,45 and another 4 studies add sustainability assessments to safety assessment without mentioning the term SSbD explicitly. 1,6,36,47 Another general finding is that most (18 out of 20) of the reviewed studies focus on engineered nanomaterials (ENMs) and nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
“…1,6,36,47 Another general finding is that most (18 out of 20) of the reviewed studies focus on engineered nanomaterials (ENMs) and nanoparticles (NPs). 1,6,16,17,[34][35][36][37][38][39][41][42][43][44][45][46][47][48] We note that all the reviewed studies have been published in between 2017-2022 and that 18 out of the 20 reviewed studies focus on nanomaterials and/or nanoparticles. This short timeframe and focus are most likely explained by the short history of the term SbD (see above) and the recent interest for nano-safety studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations